2021
DOI: 10.25083/rbl/26.3/2594.2605
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of vegetal extract characteristics from spontaneous flora of Moldova area (Romania)

Abstract: Two classical methods were applied for preparation of four plant extracts, i.e. heat reflux extraction and maceration, exactly for wormwood (Artemisia absinthium), yarrow (Achillea millefolium), oregano (Origanum vulgare) and primrose (Primula veris), plants from the spontaneous flora of Moldova area (Romania). The prepared extracts were preliminarily characterized by some known physical-chemical analytical methods used to evaluate various quality indicators of plant extracts (e.g. total polyphenols and flavon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Extraction was made using conventional and unconventional extraction procedures in the following variants: Heat Reflux Extraction (HTE), room temperature maceration (M), Ultrasound Assisted Extraction (UAE), using a work protocol (extraction time, salt/solvent ratio, and extraction solvent concentrations) established based on our previous studies [ 16 , 17 ] and after some preliminary tests were carried out (data not shown). In all the extraction techniques, 96% ethanol was used to prepare extraction solvent: hydro alcoholic solution with 30%, 50%, 70% v / v concentration.…”
Section: Methodsmentioning
confidence: 99%
“…Extraction was made using conventional and unconventional extraction procedures in the following variants: Heat Reflux Extraction (HTE), room temperature maceration (M), Ultrasound Assisted Extraction (UAE), using a work protocol (extraction time, salt/solvent ratio, and extraction solvent concentrations) established based on our previous studies [ 16 , 17 ] and after some preliminary tests were carried out (data not shown). In all the extraction techniques, 96% ethanol was used to prepare extraction solvent: hydro alcoholic solution with 30%, 50%, 70% v / v concentration.…”
Section: Methodsmentioning
confidence: 99%
“…The obtained extracts were shown to be effective in the following order: Origanum vulgare > Artemisia absinthium > Achillea millefolium > Primula veris (the last two having similar bioinsecticidal effects). The studies also showed that Origanum vulgare extract was much more effective than Artemisia absinthium in controlling the species studied, given the mortality recorded among the insects (70%) after 168 h of contact time [115].…”
Section: A New Generation Of Biopesticidal Compounds: Plant Extracts/...mentioning
confidence: 83%
“…Tests showed that the reflux extraction method in the Soxhlet apparatus performed best, with the solid/liquid (S/L) ratio and extraction time varying according to the type of plant: wormwood ( Artemisia absinthium )—1 h and S/L ratio = 1/15; horsetail ( Achillea millefolium )—2 h and S/L ratio = 1/20; oregano ( Origanum vulgare )—2 h and S/L ratio = 1/15, and primrose ( Primula veris )—2 h and S/L ratio = 1/10. Primrose ( Primula veris ) was found to exhibit the strongest bioinsecticidal character [ 112 ].…”
Section: Biopesticides: Alternatives To Synthetic Pesticides and Thei...mentioning
confidence: 99%
See 1 more Smart Citation